THE IMPLEMENTATION OF ANIMAL WELFARE STANDARDS ON PIG FARMS IN THE HIGHLANDS AND LOWLAND AREA IN GIANYAR BALI - Aribawa, I Nyoman Bagus Tri; Agustina, Kadek Karang; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana, 2024)
Animal welfare is everything related to the physical and mental state of animals in accordance with the standard of natural animal behaviour that needs to be implemented to protect animals from inappropriate treatment by humans. This study aims to determine the description of the application of animal welfare on pig farms in the highlands and lowlands in Gianyar Regency. The research design was observational by interviewing 20 farmers in each of Puhu Village (highland) and Pering Village (lowland) conducted in January 2024 using an integrated questionnaire. The data obtained were then analysed descriptively qualitatively and presented in tabular form. The Mann Whitney test was conducted to determine the difference between the application of animal welfare standards in highland and lowland areas. The results showed that the application of animal welfare on pig farms in Gianyar was in the very good category 30%, good category 65%, and fair category 5%. While the results of the comparison test found a difference in the fulfilment of the principle of free expression of the natural behaviour of pigs. It can be concluded there was a difference between the application of animal welfare standards on pig farms in the highlands and lowlands. It is recommended that pig farmers in Pering village provide enrichment facilities for pigs to express their natural behaviour.